Research on Data Gathering Algorithm Based on Fairness in Cognitive Radio Network - Xiaoming Wang; Jiankang Zhang (Dianxin kexue)
The distributed data collection problem for CRN was studied, which has not been addressed before. First, the proper carrier-sensing range（PCR）for SU was studied. By working with this PCR, a SU can successfully conduct data transmission without disturbing the activities of PU and other SU. Subsequently, based on the PCR, an asynchronous distributed data collection（ADDC）algorithm with fairness consideration for CRN was proposed. ADDC collects data of a snapshot to the base station in a distributed manner without any time synchronization requirement. The algorithm is scalable and more practical compared with centralized and synchronized algorithms. The comprehensive theoretical analysis shows that ADDC is order-optimal in terms of delay and capacity, as long as SU has a positive probability to access the spectrum. Finally, extensive simulation results indicate that ADDC can effectively finish a data collection task and significantly reduce data collection delay.